In the cystoscopic follow-up of non-muscle-invasive transitional cell carcinoma, NMP-22 works for high grades, but unreliable in low grades and upper urinary tract tumors - (:unkn) unknown (SPRINGER, 2012)
Two percent of the bladder non-muscle-invasive (NMI) transitional cell carcinomas (TCC) are associated with upper urinary tract (UUT) TCC. We evaluated the role of nuclear matrix protein-22 (NMP-22) (BladderChek(A (R))) test in the diagnosis of lower urinary tract and UUT-TCC. From March 2009 to June 2011, 122 patients with bladder NMI-TCC underwent 205 control cystoscopy. A total of 95 (78 men and 17 women, mean age 60.7 years, range, 27-88) patients who were followed regularly with NMP-22 test and with follow-up cystoscopies (145 episodes; min. 1-max. 5) were included in this study. For routine monitoring of the UUT, IVU or CT urography was used once a year for high grades (HG), and once in every other year for low grades (LG). The sensitivity and specificity of NMP-22 were evaluated by ROC curves, and sensitivity, specificity, and positive and negative predictive values were calculated. Chi-square test was used for the differences between the subgroups. Cystoscopy and NMP-22 results of the patients included in the study revealed the sensitivity (44.4%) of the test was very low and the specificity (98.4%) was quite high (p < 0.001). Among the 10 cystoscopies where NMP-22 was negative, but cystoscopy was positive for tumor, 8 had LG and 2 had HG TCC. NMP-22 was never positive in low-grade tumors, in other words, all of the NMP-22-positive 8 tumors were high grade. On the other hand, in 20% (2/10) of the cases, NMP-22 can be negative although the tumor was high grade. Two (2.1%) HG UUT-TCC were detected in 95 patients. These 2 patients were within the 125 cystoscopies (75 patients) where both NMP-22 and cystoscopy were negative for tumor. Nuclear matrix protein-22 cannot detect LG TCC. However, it detects overwhelming majority of HG TCC. For this reason, positive NMP-22 test largely indicates HG TCC. NMP-22 is also not reliable in UUT-TCC, even in HG tumors.
Keywords: NMP22; Urine marker; Bladder cancer; Upper urinary tract tumor; TCC; SUPERFICIAL BLADDER-CANCER; NUCLEAR-MATRIX PROTEIN; CARE PROTEOMIC ASSAY; UROTHELIAL CANCER; NATURAL-HISTORY; RENAL PELVIS; RISK-FACTORS; IN-SITU; SURVEILLANCE; CYTOLOGY